Character Building of Young Children in Digital Era through Media Literacy Education - Silawati, Endah; Rahman, Mohd Nazri Bin Abdul (Procedia of Social Sciences and Humanities, 2024)
In this digital era, children can access many diverse values and cultures through various media, which may have a negative impact. the information that is accessed by children will affect their perceptions, beliefs, and attitudes, which could be positive or negative [1]. As a result, having media literacy today is essential since it can immunize children through cognitive defences to guard against the damaging effects of media messages [2. For young children, media literacy education can help them to build positive character values in the digital age. Young children can have a greater awareness of many viewpoints and cultures, which promotes empathy and respect, by being taught how to critically analyse and evaluate media content [3]. Therefore, this study elaborates on how media literacy education is used as a strategy to promote positive character values of young children by kindergarten teachers. A qualitative approach was employed in this study by involving 37 kindergarten teachers around West Java Province, Indonesia. Data collection was done through questionnaires and interview methods to portray teachers’ perspective and teaching strategies in Media Literacy Education. Moreover, the validity of the data was carried out by means of triangulation. The data analysis technique was done through data reduction, data presentation, and conclusions or verification. The results showed that all of the teachers agreed that media literacy education is important for the character building of young children and to be integrated into curriculum. Furthermore, some teachers have implemented media literacy education in teaching activities in their own ways. However, there are still needs some improvement regarding teachers’ skills, learning media and digital facilities, support from policy makers and parents. Nevertheless, this study can be an initial overview for later research to investigate the further aspects of building young children's positive values in the digital world.